Diversity and selective pressures of anticoagulants in three medicinal leeches (Hirudinida: Hirudinidae, Macrobdellidae). Issue 4 (5th March 2013) - Kvist, Sebastian; Min, Gi‐Sik; Siddall, Mark E
Abstract: Although medicinal leeches have long been used as treatment for various ailments because of their potent anticoagulation factors, neither the full diversity of salivary components that inhibit coagulation, nor the evolutionary selection acting on them has been thoroughly investigated. Here, we constructed expressed sequence tag libraries from salivary glands of two species of medicinal hirudinoid leeches, Hirudo verbana and Aliolimnatis fenestrata, and identified anticoagulant‐orthologs through BLASTx searches. The data set then was augmented by the addition of a previously constructed EST library from the macrobdelloid leech Macrobdella decora . The identified orthologs then were compared and contrasted with well‐characterized anticoagulants from a variety of leeches with different feeding habits, including non‐sanguivorous species. Moreover, four different statistical methods for predicting signatures of positive and negative evolutionary pressures were used for 10 rounds each to assess the level and type of selection acting on the molecules as a whole and on specific sites. In total, sequences showing putative BLASTx‐orthology with five and three anticoagulant‐families were recovered in the A. fenestrata and H. verbana EST libraries respectively. Selection pressure analyses predicted high levels of purifying selection across the anticoagulant diversity, although a few isolated sites showed signatures of positive selection. This study represents a first attempt at mapping the anticoagulant repertoires in a comparative fashion across several leech families. Abstract : Although medicinal leeches have long been used as treatment for various ailments because of their potent anticoagulation factors, neither the full diversity of salivary components that inhibit coagulation, nor the evolutionary selection acting on them has been thoroughly investigated. Here, EST libraries from three medicinal leeches were screened for anticoagulants and putative selective pressures acting on the proteins were estimated via a series of algorithms. Results indicate that the diversity of anticoagulation factors possessed by the leeches exceeds expectations and that purifying selection heavily influences the stability of the residues.